Manajemen Fisioterapi pada Kasus Carpal Tunnel Syndrome di RS PKU Muhammadiyah Yogyakarta : Case Report - Nadhiira Dwi Amri; Galih Adhi Isak Setiawan; Mahendra Wahyu Dewangga (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Carpal Tunnel Syndrome (CTS) is a peripheral neuropathy disease that occurs due to compression or pressure on the median nerve which causes narrowing of the carpal tunnel. Common symptoms of CTS are pain, numbness, and paresthesia which usually spread to the fingers, especially the thumb, index finger, and middle finger. To determine the effectiveness of non-operative therapy in cases of Carpal Tunnel Syndrome using modalities of tools and exercise therapy in the form of nerve gliding exercise, free exercise with resistance, hand grip, and manual therapy techniques. Case report study is used as a research method by taking samples from 1 patient with a case of Carpal Tunnel Syndrome (CTS). The measuring instruments used are Visual Analog Scale (VAS) for the pain scale, Manual Muscle Testing (MMT) to measure muscle strength, Goniometer to measure Range Of Motion (ROM), and Wrist Hand Disability Index (WHDI) to measure functional activity ability. After the implementation of the 3rd therapy there were changes, namely decreased pain, increased muscle strength, increased ROM and increased functional activity. This case study shows that there is effectiveness in providing exercise therapy, manual therapy and electrotherapy in cases of Carpal Tunnel Syndrome (CTS).